2020
DOI: 10.3390/fluids5020090
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on Flexible Filaments in Air Flow for Aeroelasticity and Fluid-Structure Interaction Models Validation

Abstract: Several problems in science and engineering are characterized by the interaction between fluid flows and deformable structures. Due to their complex and multidisciplinary nature, these problems cannot normally be solved analytically and experiments are frequently of limited scope, so that numerical simulations represent the main analysis tool. Key to the advancement of numerical methods is the availability of experimental test cases for validation. This paper presents results of an experiment specifically desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The validation of the proposed theory [1][2] using the concept of zones through a simple pendulum setup was taken up in an air flow. The simple pendulum setup could be the best experimental device for quick validation of fluid structure interaction phenomenon as a similar type of validation with air, as fluid medium was performed for aero-elastic structures and NACA aero foils [8][9]. The motion of a plate pendulum can be described by an integral-differential equation, which, when integrated, transforms into a normal non-linear second-order differential equation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The validation of the proposed theory [1][2] using the concept of zones through a simple pendulum setup was taken up in an air flow. The simple pendulum setup could be the best experimental device for quick validation of fluid structure interaction phenomenon as a similar type of validation with air, as fluid medium was performed for aero-elastic structures and NACA aero foils [8][9]. The motion of a plate pendulum can be described by an integral-differential equation, which, when integrated, transforms into a normal non-linear second-order differential equation.…”
Section: Resultsmentioning
confidence: 99%
“…The structural response of the filaments was recorded. The results obtained showed that such experimental setup and approach is valuable for validation of numerical methods for aero elasticity [8]. A new CFD method based on block-iterative coupling for fluid structure interaction (Numerical aerodynamic simulation of NACA airfoil) is used.…”
Section: Introductionmentioning
confidence: 99%